A chimeric protein-based vaccine elicits a strong IgG antibody response and confers partial protection against Shiga toxin-producing Escherichia coli in mice - Montero, David A.; Garcia-Betancourt, Richard; Vidal, Roberto M.; Velasco, Juliana; Palacios, Pablo A.; Schneider, Daniela; Vega, Carolina; Gómez, Leonardo; Montecinos, Hernán; Soto-Shara, Rodrigo; Oñate, Ángel; Carreño, Leandro J. (Frontiers in Immunology, 2023)
Background: Shiga toxin-producing Escherichia coli (STEC) is a foodborne pathogen that causes gastrointestinal infections, ranging from acute diarrhea and dysentery to life-threatening diseases such as Hemolytic Uremic Syndrome. Currently, a vaccine to prevent STEC infection is an unmet medical need. Results: We developed a chimeric protein-based vaccine targeting seven virulence factors of STEC, including the Stx2B subunit, Tir, Intimin, EspA, Cah, OmpT, and AggA proteins. Immunization of mice with this vaccine candidate elicited significant humoral and cellular immune responses against STEC. High levels of specific IgG antibodies were found in the serum and feces of immunized mice. However, specific IgA antibodies were not detected in either serum or feces. Furthermore, a significantly higher percentage of antigen-specific CD4+ T cells producing IFN-γ, IL-4, and IL-17 was observed in the spleens of immunized mice. Notably, the immunized mice showed decreased shedding of STEC O157:H7 and STEC O91:H21 strains and were protected against weight loss during experimental infection. Additionally, infection with the STEC O91:H21 strain resulted in kidney damage in control unimmunized mice; however, the extent of damage was slightly lower in immunized mice. Our findings suggest that IgG antibodies induced by this vaccine candidate may have a role in inhibiting bacterial adhesion and complement-mediated killing. Conclusion: This study provides evidence that IgG responses are involved in the host defense against STEC. However, our results do not rule out that other classes of antibodies also participate in the protection against this pathogen. Additional work is needed to improve the protection conferred by our vaccine candidate and to elucidate the relevant immune responses that lead to complete protection against this pathogen.